Circulating Ideas in an Intraimperial Network From Mercantilism to Liberalism through Basque Enlightenment Thought in the Philippines - Anduaga, Aitor (Philippine Studies: Historical and Ethnographic Viewpoints, 2021)
The transition from mercantilism to economic liberalism through the Enlightenment thread offers a rare opportunity to analyze the networked circulation of ideas in the Spanish Empire. Thisarticle focuses on the circulation of knowledge by analyzing the influence of Basque Enlightenment thought in the Philippines through the lens of intraimperial networks and hybrid communities. This influence first came through the Royal Basque Society of Friends of the Country, which partly inspired the program of the Manila Economic Society, and then through the Royal Company of the Philippines, from which several Basque trading companies and a spring of free-trade proposals emerged. The Basque maritime trading diaspora favored the circulation of reformist economic ideas in the Philippines from the 1770s to the 1820s.